Clinical Characteristics, Treatment, and Visual Prognosis in Pediatric Endophthalmitis: A 232-Case Retrospective Study - Fantao Lv; Haiyan Wang; Dawei Zhang; Shengwei Wu (Applied Bionics and Biomechanics)
Objective. In infective endophthalmitis, once the patient’s vision is seriously damaged, the damage to children’s vision is particularly serious. The main purpose of this study is to investigate the etiology, epidemiology, treatment, and visual prognosis of children’s endophthalmitis and to conduct an in-depth analysis. Study Design. This study collected case data from the Beijing Tongren Hospital Capital Medical University in the period from January 1, 2002 to January 1, 2018. The basic conditions for inclusion in the collection range were patients who were less than or equal to 14 years old and had a history of infectious endophthalmitis. A retrospective study and analysis of etiology, epidemiology, treatment, and visual prognosis were performed. Kappa and Chi square test were used for statistical analysis. Results. A total of 232 cases were collected, with an average age of 6.33±2.89 years (range 8months to 14 years). The most common etiologies were ocular trauma (93.5%) and previous ocular surgery (5.2%). Overall, 81 samples were sent to the microbiology department for direct smear and culture, from which 21 organisms were isolated. 28 cases (39.5%) were culture-positive. The most organism was Gram-positive organisms. In treatment, the proportion of PPV use combined with silicone oil filling had increased gradually in three phases, while the other treatments were almost decreased or nearly similar. The final visual result is 22 (9.5) in 20/200 or better, 65 (28.0) in CF-20/200, 38 (16.4) in hand move (HM), 27 (11.6) in light perception (LP), 21 (9.1) in no light perception (NLP), and 59 (25.4) did not match (NM). Conclusion. Penetrating ocular trauma is the most common cause of infectious endophthalmitis in children. The detection rate of microorganisms is low and helpless for the treatment. In this study, it was found that despite the aggressive treatments such as antibacterial and vitrectomy, the ultimate improvement in vision was highly undesirable.